Зарни но ӟег нянь: выжыкылъёс / А. И. Кондратьев ; [художник М. В. Шарова] - Кондратьев Алексей Иванович (Удмуртия, 1985)
Экземпляры: кр (20210315) / Инвентарный номер: 9099 / Авт.знак: К 64 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Удм)6-4